2014
DOI: 10.1038/nchembio.1654
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis for selective binding of m6A RNA by the YTHDC1 YTH domain

Abstract: N(6)-methyladenosine (m(6)A) is the most abundant internal modification of nearly all eukaryotic mRNAs and has recently been reported to be recognized by the YTH domain family proteins. Here we present the crystal structures of the YTH domain of YTHDC1, a member of the YTH domain family, and its complex with an m(6)A-containing RNA. Our structural studies, together with transcriptome-wide identification of YTHDC1-binding sites and biochemical experiments, not only reveal the specific mode of m(6)A-YTH binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
646
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 604 publications
(666 citation statements)
references
References 31 publications
17
646
1
2
Order By: Relevance
“…In contrast, YTH domain family protein 1 (YTHDF1) exerts its role in promoting translation efficiency 27. In the meantime, the role of YTH domain‐containing protein 1 (YTHDC1) in regulating mRNA splicing has been revealed 28, 29. In 2017, Shi et al.…”
Section: The Discovery Of M6a and Its Functionmentioning
confidence: 99%
“…In contrast, YTH domain family protein 1 (YTHDF1) exerts its role in promoting translation efficiency 27. In the meantime, the role of YTH domain‐containing protein 1 (YTHDC1) in regulating mRNA splicing has been revealed 28, 29. In 2017, Shi et al.…”
Section: The Discovery Of M6a and Its Functionmentioning
confidence: 99%
“…Defects of the m 6 A methyltransferase complex result in a battery of development problems in various eukaryotic species (Yue et al, 2015). The YTH domain proteins, the m 6 A readers, influence the stability, translation, and splicing of the m 6 A-containing mRNAs Wang et al, 2015;Xiao et al, 2016;Xu et al, 2014;Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…3A). An aromatic cage, which is normally composed of 2-4 aromatic residues, is a signature feature of methylation reader proteins that recognize methylated lysine, arginine, and even N 6 -methyladenosine (14). Here, ZCWPW2 used 3 aromatic residues, namely Trp-30, Trp-41, and Phe-78, to read out the trimethyllysine (Fig.…”
Section: Zcwpw2 Morc3 and Morc4 Are Histone H3k4me3mentioning
confidence: 99%
“…We further determined the crystal structures of human ZCWPW2 and MORC3 CW domains in complex with H3K4me3 peptide and provide a structural explanation for the differences in the CW domain's histone binding abilities. Generally, an aromatic cage is a signature feature of methylation reader proteins that recognize methylated lysine, arginine, and even N 6 -methyladenosine (14), and it is normally composed of 2-4 aromatic residues. However, our case study of ZCWPW2 revealed that only the invariant tryptophan, a cage-forming residue of the CW domain, was essential for recognition of the methyllysine residue, whereas the other cage-forming residues play roles in enhancing binding or filtering methylation states.…”
mentioning
confidence: 99%